Analisis Flypaper Effect Pada Dana Alokasi Umum, Dana Alokasi Khusus, Dana Bagi Hasil, Dan Pendapatan Asli Daerah Terhadap Belanja Daerah Provinsi Di Indonesia - Haris Fadilah; Nayang Helmayunita (Universitas Negeri Padang, 2020)
This study aims to look at the effect of the General Allocation Fund, Special Allocation Fund, Profit Sharing Funds and Regional Original Revenue towards the Regional Expenditure and to analyze the phenomenon of the flypaper effect on the Provincial Government in Indonesia. The population of this study was 34 provinces in all provinces in Indonesia. This study used the total sampling technique. The data used were the secondary data obtained from www.djpk.kemenkeu.go.id. The method used in this study was a multiple regression by using IBM SPSS 26 program. The results of this study indicated that DAU, DBH and PAD partially have a significant positive effect on the Regional Expenditure. However, the DAK variable has no effect on the Regional Expenditure. The coefficient of Balance Fund was greater than the PAD coefficient. In conclusion, there is a flypaper effect on the provincial government in Indonesia